(untitled) (The International Journal for Scientific Research, 2026)
This study aims to analyze the impacts of the Sarat Bani Malik forest fire, south of Taif Governorate, which broke out in late May 2025, using Sentinel-2-L2A data and Geographic Information Systems (GIS) techniques through ArcGIS Pro. The study relied on the NBR and dNBR indices to identify the areas affected by the fire and classify damage severity, in addition to using NDVI and dNDVI to analyze changes in vegetation cover and monitor vegetation recovery over seven months, while utilizing the NDMI moisture index and climatic factors to explain post-fire recovery.The results showed that the affected area reached 1,133.21 hectares, with low-severity damage representing the largest proportion at 96.53%, while moderate damage reached 3.46% and high damage 0.01%. Vegetation cover area also declined from 376.38 hectares before the fire to 12.87 hectares after the fire, representing a loss of 96.6%, with partial vegetation recovery reaching approximately 15.5% by January 2026. The study contributes to supporting environmental rehabilitation efforts and guiding reforestation programs toward the most affected areas. It also represents scientific documentation of a fire event that has not been previously studied, in line with the objectives of Saudi Vision 2030 in environmental sustainability and natural resource protection.